AutoCAD for land surveyors : recommended to surveying students, engineers and employees, and cartographers - Clarke, Harriet Mac; Noormohammadi, Javad ([Las Vegas] : Independently published, 2020)
Having several years of experience in the field of land surveying and cartography of research and executive projects, the author was eager to familiarize the land surveyors with applied, fully functional AutoCAD and to help them learn the AutoCAD commands and capabilities that are practical for map drafting. I have used a lot of examples in the book for the learners and specialized exercises have also been explained in the final chapters.There is an important point to make about the presentation of the examples and exercises: It might be possible for you to find different solutions to solve the examples and exercises in the book and you might solve them using other software or methods. The purpose of presenting these examples and exercises is to help you master these commands. You can also use the commands for other purposes after mastering them.In this set of tutorials, additional topics and other parts of the software that are used in other engineering fields have been avoided.
Chapter 1. Introduction to drawing area and AutoCAD capabilities -- Chapter 2. AutoCAD General Settings -- Chapter 3. Important and useful commands -- Chapter 4. Professional settings for AutoCAD -- Chapter 5. Professional Land Surveying Practices -- Chapter 6. Answers to frequently asked questions and problems that occur when using AutoCAD.
Keywords: COMPUTER GRAPHICS; COMPUTER AIDED-DESIGN